Partituras da sinfonia contemporânea: repensando os instrumentos normativos da educação musical de Porto Alegre/RS - Silva, Fábio de Souza da (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation addresses the gaps in the normative instruments that guide music education in the public school system of Porto Alegre, especially in the context of recovery after the 2024 floods. The main objective is to analyze the normative instruments of music education for the improvement of educational management practices in the public school system of Porto Alegre. Methodologically, this is documental research, in which Bardin's content analysis was applied, focusing on the main normative documents, especially Ordem de Serviço Nº 002, to identify areas that require revision and improvement. The research adopts the theoretical framework of the "policy cycle," exploring how norms are formulated and implemented. The results indicate the need to update Ordem de Serviço Nº 002, published in the Diário Oficial de Porto Alegre on February 15, 2008, as well as to implement music programs that promote resilience and social cohesion in schools. The Political-Pedagogical Plan (PPP) is highlighted as an essential adaptive tool in this process. The dissertation concludes that music education should be recognized as a transformative and relevant tool for strengthening school communities, suggesting a collaborative approach between different government levels to ensure a more equitable and effective music education. The proposed intervention is the implementation of music programs in the public schools of Porto Alegre/RS.
Keywords: Educação musical; Instrumentos normativos; Gestão; Music education; Normative instruments; Management; ACCNPQ::Ciências Humanas::Educação